2009
DOI: 10.1042/bc20080032
|View full text |Cite
|
Sign up to set email alerts
|

A novel neuronal calcium sensor family protein, calaxin, is a potential Ca2+‐dependent regulator for the outer arm dynein of metazoan cilia and flagella

Abstract: Background information. Spermatozoa show several changes in flagellar waveform, such as upon fertilization. Ca 2+ has been shown to play critical roles in modulating the waveforms of sperm flagella. However, a Ca 2+ -binding protein in sperm flagella that regulates axonemal dyneins has not been fully characterized.Results. We identified a novel neuronal calcium sensor family protein, named calaxin (Ca 2+ -binding axonemal protein), in sperm flagella of the ascidian Ciona intestinalis. Calaxin has three EF-hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
86
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 49 publications
0
86
0
Order By: Relevance
“…[Ca 2C ] i plays key role in the regulation of flagellar beating (Darszon et al 2011). Ca 2C -dependent or CaM protein phosphatase(s) are found in flagella of sea urchin, ascidian, fish, and mammals including human sperm (Nomura et al 2004, Marín-Briggiler et al 2005, Mizuno et al 2009. Similarly, sperm motility in marine bivalve mollusks was suppressed in the presence of CaM protein phosphodiesterase antagonist.…”
Section: K7mentioning
confidence: 98%
“…[Ca 2C ] i plays key role in the regulation of flagellar beating (Darszon et al 2011). Ca 2C -dependent or CaM protein phosphatase(s) are found in flagella of sea urchin, ascidian, fish, and mammals including human sperm (Nomura et al 2004, Marín-Briggiler et al 2005, Mizuno et al 2009. Similarly, sperm motility in marine bivalve mollusks was suppressed in the presence of CaM protein phosphodiesterase antagonist.…”
Section: K7mentioning
confidence: 98%
“…The maintenance and regulation of intracellular calcium concentration ([Ca 2+ ] i ), is therefore, of great importance and is carried out by proteins and co-factors that import, export and/or sequester calcium ions [50]. In spermatozoa, swimming behavior is controlled by rises in [Ca 2+ ] i that changes flagellar beat pattern through Ca 2+ sensing proteins calaxins [51,52]. Calciumbound calaxins inhibit the activity of dynein motors within the Murine potassium channel KSper comprised of the Slo3 channel and associated gamma subunit LRRC52, as well as possible beta subunits.…”
Section: Calcium Channels and Hyperactivationmentioning
confidence: 99%
“…Pharmacological evidence indicates that CaMKII and/or CaMKIV is involved in this process in mammalian sperm (269,344). Recently, a novel Ca 2ϩ -binding protein, named calaxin, was identified as an axoneme component in sea squirt sperm (365). Bioinformatics revealed that calaxin belongs to the neuronal calcium sensor protein family.…”
Section: Flagellar Form Modulation By Ca 2ϩmentioning
confidence: 99%